On the signed $2$-independence number of graphs - S.M. Hosseini Moghaddam; D.A. Mojdeh; Babak Samadi; Lutz Volkmann (Electronic Journal of Graph Theory and Applications (EJGTA), 2017)
In this paper, we study the signed 2-independence number in graphs and give new sharp upper and lower bounds on the signed 2-independence number of a graph by a simple uniform approach. In this way, we can improve and generalize some known results in this area.